Fabrication of dense biocompatible hydroxyapatite ceramics with high hardness using a peroxide-based route: A potential process for scaling up - Randorn,C. (Elsevier Limited, 2015)
© 2015 Elsevier Ltd and Techna Group S.r.l. In this research, nanosized hydroxyapatite (HA) ceramics with high hardness at moderate temperature were prepared using a novel peroxide-based route (PBR) using calcium nitrate, phosphoric acid and hydrogen peroxide as starting materials. Single-phase HA with an average particle size of approximately 10-30 nm and a BET surface area of 23.54 m2/g were obtained after calcination at 800 °C for 2 h. Dense HA ceramics with a density of 98%, a grain size of 0.91 μm and a Vickers hardness of 5.67 GPa were achieved after sintering the HA pellet at 1,200 °C. Their biocompatibility might be anticipated by SEM images of apatite layer formation after immersion in simulated body fluid (SBF) for 14 days.